Pembelajaran Fisika Berbantuan Aplikasi Instagram untuk Meningkatkan Motivasi dan Hasil Belajar Siswa (UPEJ Unnes Physics Education Journal, 2020)
This Based on preliminary research on students of class XI MIPA Mardisiswa Semarang, it was found that the problem of learning motivation and learning outcomes was still low. One way to solve the problem by using audio visual learning media. The fact is students' interest in Instagram is very high. This can be as a learning innovation. In Instagram, students get animated videos and infographics so learning can be more fun. The purpose of this study is to determine the increase in motivation, learning outcomes and student responses after Instagram-assisted learning. This type of research is a Quasy Experimental with Nonequivalent Control Group Design. The results of the N-Gain for pretest and posttest showed an increase in motivation after Instagram-assisted physics learning was implemented by 0.55 or in the â€œmedium criteriaâ€. While increasing learning outcomes by 0.73 or â€œhigh criteriaâ€. Student response test after applied learning assisted by Instagram obtained a percentage of 82.87% with the category "very good". In conclution, learning assisted by Instagram can be used to improve student learning outcomes and motivation.